Preparation of Cu(II), Ni(II), Ti(IV), VO(IV), and Zn(II) Metal Complexes Derived from Novel vic-Dioxime and Investigation of Their Antioxidant and Antibacterial Activities - Alhafez, Anas; Savcı, Ahmet; Alan, Yusuf; Söylemez, Rahime; Kılıç, Ahmet (Wiley-V C H Verlag Gmbh, 2022)
In this work, novel vic-dioxime ligand (LH2) containing bound to the N-4-oxime core moiety and its complexes with Cu(II), Ni(II), Ti(IV), VO(IV), and Zn(II) salts have been studied. The structure of the ligand and its complexes were successfully synthesized and characterized using NMR (H-1 and C-13), LC/MS/MS spectrometer, FT-IR and UV/VIS spectroscopy, melting point, and magnetic susceptibility measurements. Vic-dioxime ligand (LH2) (1) and its metal complexes ([Cu(LH)(2)] (2), [Ni(LH)(2)] (3), [Ti(LH)(2)]Cl-2 (4), [VO(LH)(2)] (5), and [Zn(LH)(2)] (6), respectively) were tested for them in-vitro antibacterial and antioxidant activities. According to the metal chelating results of the study, it was determined that compounds (1), (2), (3), and (6) showed very good activity, and especially compound (2), had a stronger metal chelating capacity due to ligand dissociation from the synthesized metal complexes, which then would chelate Fe(II) in the experimental setting. When microorganisms were evaluated in terms of the % viability effect, it was observed that all compounds had activity against C. Albicans and S. Cerevisiae at rates similar to antibiotics.
Keywords: vic-dioxime; metal complexes; spectroscopy; antimicrobial activity; antioxidant activity; Antimicrobial Activities; Dna-Binding; Oxime; Nickel(Ii); Copper(Ii); Capacity; Co2